2022
DOI: 10.3389/fphar.2021.805318
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nonselective Beta-Blocker Use and Hepatocellular Carcinoma in Patients With Chronic Hepatitis B Without Cirrhosis and Decompensation

Abstract: Background: Nonselective beta-blockers (NSBBs) can reduce the incidence or mortality of certain types of cancers, and NSBBs exert a protective effect on hepatocellular carcinoma (HCC) in patients with cirrhosis. However, the potential preventive effect of NSBBs has not yet been investigated in patients with chronic hepatitis B (CHB) who have a high HCC risk regardless of the presence of underlying cirrhosis.Aim: This study evaluated the association between NSBB use and HCC incidence in patients with CHB withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Most cases were treated with CCBs or ARBs, and beta-blockers were used in few cases. The recent studies proved that beta-blockers not only prevented the variceal bleeding but also improved the prognosis of patients with cirrhosis [21][22][23], but in Japan, the administration of beta-blockers tends to be avoided due to concerns about symptoms caused by their hypotensive effects, and this was demonstrated in this study. Based on the result of animal models that showed the anti-fibrotic effects of ACEI and ARB, the impact of these agents on the liver-related events in non-alcoholic fatty liver disease was evaluated.…”
Section: Discussionmentioning
confidence: 62%
“…Most cases were treated with CCBs or ARBs, and beta-blockers were used in few cases. The recent studies proved that beta-blockers not only prevented the variceal bleeding but also improved the prognosis of patients with cirrhosis [21][22][23], but in Japan, the administration of beta-blockers tends to be avoided due to concerns about symptoms caused by their hypotensive effects, and this was demonstrated in this study. Based on the result of animal models that showed the anti-fibrotic effects of ACEI and ARB, the impact of these agents on the liver-related events in non-alcoholic fatty liver disease was evaluated.…”
Section: Discussionmentioning
confidence: 62%
“…It has been shown that non-selective β-blockers demonstrated lower frequency or mortality of the solid tumors, including the upper gastrointestinal cancers in clinical and human research studies. 63 Propranolol, a nonselective β-blocker, exhibits a potential in reducing oxidative stress and pro-tumorigenic inflammatory response. It also inhibits tumorigenesis through a variety of molecular and cellular mechanisms that are dependent on concentration and time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more effective strategies are demanded. It has been shown that non‐selective β‐blockers demonstrated lower frequency or mortality of the solid tumors, including the upper gastrointestinal cancers in clinical and human research studies 63 . Propranolol, a non‐selective β‐blocker, exhibits a potential in reducing oxidative stress and pro‐tumorigenic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments it inhibited nuclear translocation of ERK despite its effect on ERK phosphorylation ( 68 ). The effect of NSBB on HCC development is under debate ( 69 , 70 ). Here, it would be interesting to have more specific data for carvedilol.…”
Section: Beta-arrestin Biased Signaling and Carvedilolmentioning
confidence: 99%